Avaliação sazonal da extração e microencapsulação do óleo essencial de capim limão (Cymbopogon citratus (D.C.) Stapf.) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
Lemongrass (Cymbopogon citratus) is an aromatic plant of great significance in the pharmaceutical, cosmetic and food industries, due to its essential oil characteristic aroma and therapeutic properties. Essential oils are a mixture of volatile substances, produced by plants secondary metabolism, with low chemical stability if exposed to air, light and humidity, which encapsulation techniques can improve. Thus, this study aimed to evaluate the seasonal influence in the yield and concentration of the predominant component citral of C. citratus essential oil and to develop microcapsules by spray drying containing this vegetal product. Lemongrass leaves were collected in the four seasons, and the essential oil was extracted by hydrodistillation. The chemical composition was determined by gas chromatography with flame ionization detection (GC-FID) and by gas chromatography mass spectrometry (GC-MS). In spring and summer, the highest concentrations of citral (chemical and biological marker of the species) were obtained (84.89% and 79.39%, respectively), as well as the highest yields. For encapsulation, different proportions of arabic gum and guar gum were evaluated as wall/encapsulating materials, and the maltodextrin was added as a drying aid and cryoprotectant. Physicochemical analyses characterized the microparticle powder. By GC-MS, it was possible to identify a high concentration of citral in the microparticles, confirming the presence of the essential oil. Field-emission scanning electron microscopy showed agglomerated microparticles, with no visible fractures or fissures. Fourier transform infrared spectroscopy suggested the essential oil encapsulation due to the presence of a band at 1675 cm-1 used as a reference, related to the acyclic monoterpenes of citral. In X-ray diffraction, the microparticles showed an amorphous structure. By thermogravimetry, it was observed that the microparticles showed a higher degradation temperature than observed in the pure essential oil, inferring that encapsulation improved its thermal stability, and evidenced the cryoprotective effect of maltodextrin. The results were satisfactory, confirming the effectiveness of lemongrass essential oil microencapsulation, and supporting the potential application of this technology in food, pharmaceutical or cosmetic products.
Keywords: avaliação sazonal; citral; encapsulação; tecnologia farmacêutica; inovação tecnológica; seasonal evaluation; citral; encapsulation; pharmaceutical technology; tecnologic innovation; CNPQ::CIENCIAS DA SAUDE::FARMACIA